PCR-based tests for the early diagnosis of sepsis. Where do we stand?. Issue 6 (December 2017) - Ginn, Andrew N.; Halliday, Catriona L.; Douglas, Abby P.; Chen, Sharon C-A.
Abstract : Purpose of review: Bloodstream infections are a major cause of hospital and ICU admission with high morbidity and mortality; however, early and targeted antimicrobial therapy reduces mortality in high-risk patients. This article focuses on the diagnosis of bloodstream infections by PCR-based approaches at an early stage to enable prompt treatment and prevent organ dysfunction. Recent findings: PCR systems offering highly multiplexed targeting of bacterial and/or fungal pathogens (in whole blood) offer the best opportunity for clinical impact, as informed decisions can be made within 4–8 h of the blood draw. Although more rapid, these systems are typically associated with lower sensitivity and specificity than postculture detection methods which rely on microbial growth. Additionally, unlike postculture methods, detection directly from blood is not prone to misleading results because of concurrent (or previous) therapy, which limit clinical relevance. Summary: Rapid and accurate identification of the cause of sepsis is essential in improving patient outcomes. Early identification of these pathogens by nucleic acid detection assays directly from blood samples remains key to achieving this, particularly if taken at the time of presentation. Selection of the most suitable PCR system is typically influenced by local epidemiology and by the resources of the testing laboratory.